Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1021/cg701022e
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in Carbamazepine Cocrystals

Abstract: Cocrystals of carbamazepine with nicotinamide and saccharin are shown to be polymorphic. Two polymorphs of carbamazepine-nicotinamide (CBZ-NCT) cocrystals and two polymorphs of carbamazepine-saccharin (CBZ-SAC) cocrystals were grown from solution in the presence of polymer heteronuclei. The two CBZ-NCT polymorphs, CBZ-NCT I and a polymer nucleated (PN) form of CBZ-NCT, were characterized by Raman spectroscopy and powder X-ray diffraction. CBZ-SAC II, a new polymorph, was found to be in the monoclinic space gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
176
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(193 citation statements)
references
References 14 publications
13
176
0
1
Order By: Relevance
“…Nicotinamide has been utilized as a coformer for the cocrystallization of celecoxib (15), theophylline (16), ibuprofen (17), CBZ (18,19), and lamotrigine (20). Reported methods of cocrystal preparation are solution cooling crystallization (21), ambient co-milling (18), cryogenic co-grinding (22), melting (23), and solvent evaporation (24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicotinamide has been utilized as a coformer for the cocrystallization of celecoxib (15), theophylline (16), ibuprofen (17), CBZ (18,19), and lamotrigine (20). Reported methods of cocrystal preparation are solution cooling crystallization (21), ambient co-milling (18), cryogenic co-grinding (22), melting (23), and solvent evaporation (24).…”
Section: Introductionmentioning
confidence: 99%
“…Although CBZ and nicotinamide (NCT) cocrystals have been reported in the literature (18,19), there is a dearth of published information regarding their physicochemical, mechanical, and stability properties. Thus, it is important to evaluate these properties prior to product development in order to select an appropriate dosage form.…”
Section: Introductionmentioning
confidence: 99%
“…Na Farmacopeia Brasileira, os di-zeres recomendados pelo ICH (Guidance, 1987) quanto à presença de polimorfismo estão presentes para dois fármacos, cloridrato de ranitidina e zidovudina, e a técnica analítica utilizada na distinção dos polimorfos é a espectrometria de infravermelho. 51,52 Além disso, durante o processo de fabricação do medicamento, algumas etapas de procedimento podem levar a alterações polimór-ficas, tais como, processo de micronização ou moagem; granulação via úmida, secagem, compressão e descontaminação microbiológica com irradiação gama. Desta forma, além da caracterização inicial do fármaco ao chegar à fábrica, é importante avaliar se o processo produtivo também pode alterar a forma polimorfa.…”
Section: Polimorfismounclassified
“…22,26 In fact, the number of reports of cocrystal polymorphism is similar to that for single component phases, 27,28 and any historical differences are more likely to be due to difficulties associated with screening for different polymorphic forms of cocrystals than to an inherent tendency for cocrystals to be monomorphic. 13, 29 Cocrystal stability is not yet well understood, but studies have shown that cocrystals can dissociate spontaneously on heating or through partial dissolution of one of the coformers. 2,24,25,[30][31][32] Theophylline is a pharmaceutically active compound used as a treatment for asthma and COPD for which seven polymorphic forms have been reported.…”
Section: Introductionmentioning
confidence: 99%